Authentic Assessment in The Pandemic Period - Das Salirawati (Journal of The Indonesian Society of Integrated Chemistry, 2021)
The pandemic period was resulted in a sudden change from an offline to an online learning system without any preparation. This condition requires educators to harmonize the assessment system carried out so that it is suitable and relevant to the current pandemic era. Educators should be able to find a new formula for conducting assessments that are easy, simple, but still represent the student competency. This article provides strategies for how to perform authentic assessments in online learning in the pandemic era. This research is a descriptive study that focuses on solving actual problems encountered by educators (teachers) when learning takes place online due to the pandemic. Several authentic assessments that can be performed are (1) giving simple quizzes frequently, (2) giving assignments at the end of online learning activities, as detecting students' understanding of the material presented, (3) making variations in the form of questions and assignments so that students don't get bored, excited, and interested in studying, and (4) deliberating for deadlines and increasing the number of test questions/exams.